2010
DOI: 10.1002/cne.22378
|View full text |Cite
|
Sign up to set email alerts
|

Sciatic nerve injury in adult rats causes distinct changes in the central projections of sensory neurons expressing different glial cell line‐derived neurotrophic factor family receptors

Abstract: Most small unmyelinated neurons in adult rat dorsal ganglia (DRG) express one or more of the coreceptors targeted by glial cell line-derived neurotrophic factor (GDNF), neurturin and artemin (GFRα1, GFRα2 and GFRα3 respectively). The function of these GDNF family ligands (GFLs) is not fully elucidated but recent evidence suggests GFLs could function in sensory neuron regeneration after nerve injury and peripheral nociceptor sensitisation. In this study, we used immunohistochemistry to determine if the DRG neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 81 publications
2
43
2
Order By: Relevance
“…Several earlier studies reported an increase in the number of cells expressing GFRα3 after injury (3,8,14,26). In contrast, we found decreased GFRα3 levels in DRG neurons shortly after DR crush that persisted for at least 12 d (Fig.…”
Section: Discussioncontrasting
confidence: 39%
See 4 more Smart Citations
“…Several earlier studies reported an increase in the number of cells expressing GFRα3 after injury (3,8,14,26). In contrast, we found decreased GFRα3 levels in DRG neurons shortly after DR crush that persisted for at least 12 d (Fig.…”
Section: Discussioncontrasting
confidence: 39%
“…Some previous studies have suggested that GFRα3, the high-affinity binding partner of ARTN, is expressed predominantly in small, unmyelinated sensory neurons, with limited to no expression in large, myelinated neurons (8,9,13,14). Nevertheless, myelinated fibers regenerate after ARTN treatment, suggesting that GFRα3 may be more widely expressed than previously reported.…”
Section: Gfrα3 Is Present In Both Myelinated and Unmyelinated Sensorymentioning
confidence: 80%
See 3 more Smart Citations